Deep Neural Network Concepts for Classification using Convolutional Neural Network: A Systematic Review and Evaluation - Galety, Mohammad; Al Mukthar, Firas Husham; Maaroof, Rebaz Jamal; Rofoo, Fanar (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
In recent years, artificial intelligence (AI) has piqued the curiosity of researchers. Convolutional Neural Networks (CNN) is a deep learning (DL) approach commonly utilized to solve problems. In standard machine learning tasks, biologically inspired computational models surpass prior types of artificial intelligence by a considerable margin. The Convolutional Neural Network (CNN) is one of the most stunning types of ANN architecture. The goal of this research is to provide information and expertise on many areas of CNN. Understanding the concepts, benefits, and limitations of CNN is critical for maximizing its potential to improve image categorization performance. This article has integrated the usage of a mathematical object called covering arrays to construct the set of ideal parameters for neural network design due to the complexity of the tuning process for the correct selection of the parameters used for this form of neural network.